Chronic pain with neuropathic characteristics after surgery for major trauma to the lower limb: prevalence, predictors and association with pain severity, disability and quality of life in the UK WHiST trial - Keene, D; Knight, R; Bruce, J; Dutton, S; Tutton, E; Achten, J; Costa, M (British Editorial Society of Bone and Joint Surgery, 2021)
Aims To identify the prevalence of neuropathic pain after lower limb fracture surgery, assess associations with pain severity, quality of life and disability, and determine baseline predictors of chronic neuropathic pain at three and at six months post-injury.